Vida Saludable: ¿Está usted en riesgo de deshidratación? - Jennifer Hillan; Linda B. Bobroff (EDIS)
Revised! FCS8847-Span, a 1-page fact sheet by Jennifer Hillan and Linda B. Bobroff, is the Spanish version of “Healthy Living: Are You At Risk of Dehydration?” (FCS8847). It provides a list of questions elders can ask themselves to determine whether they are at risk for dehydration and offers suggestions for staying hydrated. Published by the UF Department of Family, Youth and Community Sciences, September 2010.